2022
DOI: 10.3390/ma15196526
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Full-Scale Laminated Veneer Lumber Beams with CFRP Sheets

Abstract: This paper presents the results of experimental research on full-size laminated veneer lumber (LVL) beams unreinforced and reinforced with CFRP sheets. The nominal dimensions of the tested beams were 45 mm × 200 mm × 3400 mm. The beams were reinforced using the so-called U-type reinforcement in three configurations, differing from each other in the thickness of the reinforcement and the side surface coverage. An epoxy resin adhesive was used to bond all the components together. A four-point static bending test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Thus, the flatwise position tested samples did not reach higher values than the edgewise position in MOE results. The bending test load-deflection curves of the flatwise and edgewise positions samples demonstrated that the FRP-LVL panels exhibited increased maximum load and maximum deflection when compared to the LVL panels (Figures 6 and 7); these results are consistent with the results of the authors Bakalarz and Kossakowski [54] who also obtained higher maximum load and deflection values for FRP-LVL compared to the control LVL.…”
Section: Mechanical Properties 331 Strength and Stiffness Bending Pro...supporting
confidence: 88%
“…Thus, the flatwise position tested samples did not reach higher values than the edgewise position in MOE results. The bending test load-deflection curves of the flatwise and edgewise positions samples demonstrated that the FRP-LVL panels exhibited increased maximum load and maximum deflection when compared to the LVL panels (Figures 6 and 7); these results are consistent with the results of the authors Bakalarz and Kossakowski [54] who also obtained higher maximum load and deflection values for FRP-LVL compared to the control LVL.…”
Section: Mechanical Properties 331 Strength and Stiffness Bending Pro...supporting
confidence: 88%
“…z o.o. from Malbork, Poland) that was tested by the authors for strengthening timber structures in past experiments [ 14 , 15 ]; it is proven to be a reliable solution. The size of the tested specimens (LVL) was assumed taking into account the economic reasons and preliminary character of the study.…”
Section: Methodsmentioning
confidence: 99%
“…In civil engineering, a common way to rehabilitate, strengthen, and optimize a new and existing structure is by adding an additional element. These additional elements can be made of steel [ 12 ], aluminum, or composite materials such as composites reinforced with aramid, glass [ 13 ], basalt, and carbon fibers [ 14 , 15 ]. The reinforcement can be positioned symmetrically or asymmetrically in the tensile or/and in the compression zone.…”
Section: Introductionmentioning
confidence: 99%
“…Each series consists of five beams. The beam testing procedure is presented in detail in [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The studies described above were focused on the analysis of solid and glue laminated timber beams strengthened with composite and steel materials. A limited number of works were devoted to the strengthening of laminated veneer lumber beams with composite materials [ 6 , 23 , 24 , 25 , 26 , 27 ]. Therefore, the main aim of this article is to create a comprehensive study that includes analysis of the strain, stiffness and ductility of full-scale laminated veneer lumber LVL beams strengthened with CFRP.…”
Section: Introductionmentioning
confidence: 99%